Book review "Petroleum Production Engineering" (Rudarsko-geološko-naftni zbornik, 2016)
Here is given the review of the book „Petroleum Production Engineering“ written by Marin Čikeš, Ph. D., a retired Full Professor of the Faculty of Mining, Geology and Petroleum Engineering of the University of Zagreb. The book was published in the year 2015, as a university textbook (Manualia universitatis studiorum Zagrabiensis).